2022
DOI: 10.1002/cey2.218
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized multifunctional phase change materials based on carbonized Cu‐coated melamine foam/reduced graphene oxide framework for multiple energy conversion and storage

Abstract: The leakage of organic phase change materials (OPCMs) at temperatures above their melting point severely limits their large-scale application. The introduction of porous supports has been identified as an efficient leakageproofing method. In this study, a novel carbonized Cu-coated melamine foam (MF)/reduced graphene oxide (rGO) framework (MF/rGO/Cu-C) is constructed as a support for fabricating stabilized multifunctional OPCMs. MF serves as the supporting material, while rGO and Cu act as functional reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 46 publications
(76 reference statements)
0
20
0
Order By: Relevance
“…3f), suggesting that the capping of TA molecules improves the electronegativity of SnO 2 -TA NPs. 58,59 The TEM images of SnO 2 NPs-TA (Fig. 3g and h) exhibit a slightly better dispersion than the SnO 2 NPs (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…3f), suggesting that the capping of TA molecules improves the electronegativity of SnO 2 -TA NPs. 58,59 The TEM images of SnO 2 NPs-TA (Fig. 3g and h) exhibit a slightly better dispersion than the SnO 2 NPs (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…[37][38][39] PCMs can effectively harvest thermal energy by a solid-liquid transition, which have been intensively explored for advanced utilization in solar-thermal conversion, electric-thermal conversion, magnetic-thermal conversion, and thermal management of electronics. [40][41][42][43] Numerous studies have focused on achieving improvements in TE conversion performance and thermal energy conversion efficiency of PCMs. [44][45][46][47] Notably, the integration of multiple thermal energy sources freely existing in the environment for multiple purposes is another approach to achieve carbon neutrality.…”
Section: Introductionmentioning
confidence: 99%
“…23 Hu et al constructed a novel Cu-coated carbonized melamine foam/reduced graphene oxide, which was used as the supporting framework for preparing PCC and exhibited good photothermal and electrothermal conversion capabilities, thermal cycling stability, and shape stability. 24 Wang et al investigated the embedding of PW into the Cu foam to form a PCC, and the results showed that the Cu foam can effectively improve the heat transfer uniformity inside PW and reduce the heat storage time by 40%. 25 Among those supporting additives, porous Cu is commonly used as a conductively supporting framework for accommodating PCMs due to its high thermal conductivity and good mechanical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Buonomo et al used a numerical study method to investigate the effect of Al foam and ceramic nanoparticles together on enhancing the heat transfer properties of the system, and the results indicated that the metal foam significantly improved the heat transfer between the PCM and the heat transfer fluid related to the addition of nanoparticles . Hu et al constructed a novel Cu-coated carbonized melamine foam/reduced graphene oxide, which was used as the supporting framework for preparing PCC and exhibited good photothermal and electrothermal conversion capabilities, thermal cycling stability, and shape stability . Wang et al investigated the embedding of PW into the Cu foam to form a PCC, and the results showed that the Cu foam can effectively improve the heat transfer uniformity inside PW and reduce the heat storage time by 40% …”
Section: Introductionmentioning
confidence: 99%